Incidence of insect pests of turmeric (Curcuma longa L.) in northern Karnataka, India - Kulkarni, Y K Kotikal, K A (Journal of Spices and Aromatic Crops, 2000)
A roving survey conducted during 1996-97 at three phases of crop growth in turmeric (Curcuma longa) in northern districts of Kamataka (India) revealed the incidence of major insect pests like rhizome fly (Mimegralla coeruleifrons), shoot borer (Conogethes punctiferalis), lacewing bug (Stephanitis typicus), leaf roller (Udaspes folus), thrips (Panchaetothrips indicus) and scale insects (Aspidiotus curcumae) in all the areas and minor pests like various species of leaf beetles, caterpillars and grasshoppers. The population of rhizome fly was high (up to 0.88 adults per m2) in Raibag, Athani, Mudhol, Indi, Chincholli and Basavakalyan taluks at all stages of crop growth. However, most of the rhizomes that contained maggots of rhizome fly were rotten. Shoot borer was predominant in early vegetative phase (45-60 days) and grand growth stage (100-120 days) of the crop in Raibag, Chikodi, Jamakhandi, Indi and Humanabad taluks.